Інтелектуальна власність у господарській системі розвитку України - Щокін, Ростислав Георгійович (My University, 2012)
Доводиться, що інтелектуальна власність є економічною цінністю суспільства, а тому необхідно створити належні умови для реалізації та охорони права інтелектуальної власності. Зростанню інтелектуального потенціалу держави повинно максимально сприяти її законодавство. Право на інтелектуальну власність має бути не лише закріплене законами України, а й охоронятися державою. It is proved that intellectual property is an economic value of society, and therefore it is necessary to create appropriate conditions for the implementation and protection of intellectual property rights. The growth of the intellectual potential of the state should be maximally facilitated by its legislation. The right to intellectual property should not only be enshrined in the laws of Ukraine, but also protected by the state.
Keywords: інтелектуальна власність; intellectual property; господарська система; economic system; Україна; Ukraine; розвиток України; development of Ukraine